Perencanaan Pengembangan Sistem Distribusi Air Bersih Pada PDAM Bersujud Tanah Bumbu di Unit BNA Batulicin - Hikami, Ghofi Reis (Jernih: Jurnal Tugas Akhir Mahasiswa, 2024)
In 2021 PDAM Bersujud Tanah Bumbu in the Batulicin BNA unit recorded a watertreatment discharge of 270 L/d, while the maximum daily demand discharge is 206 L/d, meaningthat there is still 54 L/d of water that should be used for the development of distribution networks,and also in that year the coverage of clean water distribution services in the Batulcin District wasrelatively small, namely 39%, this was because many people in the Batulicin sub-district usedground water or drilled wells. continuous use of groundwater is not recommended, according toLaw no. 7 of 2004 article 34 concerning Groundwater states that groundwater is one of the waterresources whose existence is limited and its damage results in extensive impacts and its recoveryis difficult. So that at BNA Batulicin it is necessary to carry out a plan for the development of aclean water distribution system. Planning is carried out for 9 years in accordance with VillageSDG's with a target of maximum service coverage or 100% until 2030. Planning is divided into 2stages, namely in 2021 to 2026, and in 2026 to 2030. Calculation of water needs is calculatedfrom population projections by arithmetic and geometric methods. From the results of calculatingthe water needs of BNA Batulicin in 2030 with a total population of 139,709 people, the averagewater requirement is 328 L/d, the peak hour requirement is 492 L/d, and the maximum dailyrequirement is 361 L/d.. Hydraulic simulation in the end of the pipeline network planning iscarried out with the EPANET 2.0 application, with the result that it meets the water flow technique,namely the pressure parameter of 96% node is worth 10 – 30 mka and 4% is worth 30 – 50 mka,while the pressure loss parameter is 40% is < 0.01 m/km, 31% is worth 0.01 – 1 m/km, 15% isworth 1 – 4 m/km and 13% is worth 4 – 10 m/kmKeywords : PDAM, EPANET 2.0, DistributionNetwork.